Waveguide properties recovered from shallow diffractions in common offset GPR - Strobach, Elmar; Harris, Brett; Dupuis, Christian; Kepic, Anton (Wiley-Blackwell Publishing Inc., 2013)
Near-surface heterogeneities produce diffractions in common offset ground-penetrating radar (GPR) data from the Gnangara Groundwater Mound, north of Perth, Western Australia. These diffracted wavefields can be enhanced and show a dispersion pattern if they propagate along a waveguide caused by a low velocity surface layer, such as moist sand on top of dry sand. Until now, GPR waveguide dispersion has been analyzed and inverted using common midpoint data. Using numerical modeling, we demonstrate that the same dispersion information can also be recovered from a diffracted electromagnetic wavefield recorded with common offset geometry. Frequency-slowness analysis of shallow diffractions in common offset GPR field data reveals high resolution dispersion curves. Inverting picked dispersion maxima to modeled curves (i.e., modal wave propagation in waveguide layer) allows estimation of waveguide height and velocities of waveguide and the underlying material. Data analysis in the frequency-wavenumber domain provides an alternative technique for extracting dispersion curves. Preliminary results validate this approach, which could be favorable in large-scale applications due to minimal processing requirement and inherent yet adjustable spatial averaging. The differences between waveguide parameters recovered from two surveys appear to be consistent with seasonal changes in moisture content and lateral changes due to variations in depositional environment.Our approach presents a new method to quantify the shallow dielectric permittivity structure of the subsurface from common offset gathers—the most commonly acquired type of GPR data. Potential applications of this method include estimation of shallow moisture distribution, early target identification for unexploded ordnance (UXO) detection, concrete slab characterization, pedological investigations, or planetary exploration.